Proceedings of the 17 Th International Symposium on Management (INSYMA 2020) 2020
DOI: 10.2991/aebmr.k.200127.094
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gender Diversity on Company Financial Performance

Abstract: This study aims to examine the effect of gender diversity on the board of commissioners and board of directors on the financial performance of non-financial companies listed on the Indonesia Stock Exchange over the period of 2013-2017. The analytical method used was multiple linear regressions with the classical assumption test. As a result, the presence of women on the board of directors and board of commissioners measured by dummy and the proportion of women councils did not affect financial performance as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…However, it must be noted the results are novel and thus contribute to body of knowledge. Several scholars failed to find any significant results (see (Ekadah & Mboya, 2011;Gallego-Álvarez et al, 2010;Marashdeh et al, 2021;Musa et al, 2020;Satria et al, 2020;Suherman et al, 2021;Siagbian, 2018;Zaid et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it must be noted the results are novel and thus contribute to body of knowledge. Several scholars failed to find any significant results (see (Ekadah & Mboya, 2011;Gallego-Álvarez et al, 2010;Marashdeh et al, 2021;Musa et al, 2020;Satria et al, 2020;Suherman et al, 2021;Siagbian, 2018;Zaid et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Musa et al (2020) examined the effect of board gender diversity in Nigerian banks and concluded that there is no significant effect on their financial performance. Also, Satria et al (2020) examined the link between board gender diversity and financial performance using non-financial corporations in Indonesia from 2013 to 2017 and found no significant effect. Furthermore, Gao (2020) examined 17,075 Chinese firms over a period of 2010 to 2016 and established that women directors have positive significant effect on financial performance.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the studies carried out by LISAIME, [1] which declares gender diversity has an adverse impact on profitability. Meanwhile, research from Maghfiroh & Utomo, [25] states that gender diversity does not affect profitability. Research conducted by Fitri & Erlita,[26] states that gender diversity has a positive effect on capital structure.…”
Section: Fig 1 Graphics Historical Performance Consumer Non Cyclicalmentioning
confidence: 99%